Local knowledge of traditional fishermen on economically important crabs (Decapoda: Brachyura) in the city of Conde, Bahia State, Northeastern Brazil - de Magalhães Henrique; Neto Eraldo Medeiros; Schiavetti Alexandre (BMC, 2012)
Abstract Background This article records the traditional knowledge of crab gatherers in the city of Conde, in the North Coast Region of Bahia State, Northeastern Brazil. Methods Data on biological and ecological aspects of economically important brachyuran crustaceans have been obtained from semi-structured interviews and in loco observations conducted from September 2007 to December 2009. A total of 57 fishermen of both genders, aged between 10 and 78 years have been interviewed (individually or collectively) in different contexts; interviewees were asked about aspects such as external morphology, life cycle, trophic ecology, and spatial and temporal distribution of the major economically important brachyuran crustaceans in the region. Seven fishing communities were visited: Siribinha, Sítio do Conde, Poças, Ilha das Ostras, Cobó, Buri and Sempre Viva. Data were analyzed by comparing the information provided by participants with those from the specialized academic literature. Results The results show that artisanal fishermen have a wide ranging and well-grounded knowledge on the ecological and biological aspects of crustaceans. Crab gatherers of Conde know about growth and reproductive behavior of the animals they interact with, especially with regard to the three major biological aspects: "molt", "walking dance" and "spawning". Conclusion This knowledge constitutes an important source of information that should be considered in studies of management and sustainable use of fishery resources in the North Coast Region of Bahia State.